Analysis of enamel surface damage after selective laser ablation of composite from tooth surfaces - Chan, Kenneth H. (2013)
OBJECTIVE: Resin-based composites are used for many applications in dentistry. They are difficult to remove without damage to the underlying enamel since they adhere strongly and are color matched to the tooth. The objective of this study was to determine if an automated laser scanning system with spectral feedback could be used for selective removal of residual orthodontic composite from tooth surfaces with minimal damage to the underlying enamel. MATERIALS AND METHODS: A CO(2) laser operating at a wavelength of 9.3 μm with a pulse duration of 10–15 μs and a pulse repetition rate of ~200 Hz was used to selectively remove composite from the buccal surfaces of extracted teeth. A spectral feedback system utilizing a miniature spectrometer was used to control the laser scanning system. Pulpal temperature measurements were performed during composite removal to determine if there was excessive heat accumulation. Conventional and digital microscopes were used to assess the amount of enamel lost during removal. RESULTS: The amount of enamel lost averaged between 20 and 25 μm for irradiation intensities from 3.8 to 4.2 J/cm(2), respectively. An average maximum temperature rise of 1.9±1.5°C was recorded, with no teeth approaching the critical value of 5.5°C. The average time for composite removal from an area of 5 mm(2) was 19.3±4.1 s, fast enough for clinical feasibility. CONCLUSION: Residual composite can be rapidly removed from tooth surfaces using a CO(2) laser with spectral feedback, with minimal temperature rise within the pulp and with minimal loss of sound enamel.